DEVELOPING STUDENTS’ CREATIVE ACTIVITY THROUGH LANDSCAPE DRAWING IN ART EDUCATION - Tursunova Dilshoda Jahongirovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Annotation: This article explores methods for enhancing students’ creative activity through landscape drawing in art education. It examines pedagogical approaches, didactic strategies, and practical exercises that help students develop technical skills, compositional understanding, and imaginative thinking. The study highlights how landscape drawing can stimulate creativity, visual perception, and aesthetic appreciation, while also promoting independent and collaborative work in classroom settings.